2017
DOI: 10.1200/jco.2016.71.8726
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic and Prognostic Implications of BRAF V600E in Pediatric Low-Grade Gliomas

Abstract: Purpose BRAF V600E is a potentially highly targetable mutation detected in a subset of pediatric low-grade gliomas (PLGGs). Its biologic and clinical effect within this diverse group of tumors remains unknown. Patients and MethodsA combined clinical and genetic institutional study of patients with PLGGs with long-term follow-up was performed (N = 510). Clinical and treatment data of patients with BRAF V600E mutated PLGG (n = 99) were compared with a large international independent cohort of patients with BRAF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
252
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 265 publications
(279 citation statements)
references
References 37 publications
6
252
0
8
Order By: Relevance
“…Since then multiple other activating alterations of RAS/MAPK pathway have been described in pediatric LGG, and it has been suggested that LGGs of childhood are a single pathway disease (Fig. ) …”
Section: Epidemiologymentioning
confidence: 99%
“…Since then multiple other activating alterations of RAS/MAPK pathway have been described in pediatric LGG, and it has been suggested that LGGs of childhood are a single pathway disease (Fig. ) …”
Section: Epidemiologymentioning
confidence: 99%
“…Although biopsy of the initial cystic lesion was not performed, if these molecular abnormalities had been detected, the malignant transformation may have been predicted. In addition, our patient may have been able to be treated with BRAF inhibitors, which have a higher response rate for low‐grade gliomas with BRAF V600E mutation …”
Section: Discussionmentioning
confidence: 99%
“…We were not able to find a confounding factor, such as age or NF1 status, which could have accounted for this difference. It is possible that patients with BRAFV600E mutation, known to have a worse prognosis, could have been overrepresented in the dose‐reduced group . We were, however, limited by the retrospective nature of the study and it was not possible to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that patients with BRAFV600E mutation, known to have a worse prognosis, could have been overrepresented in the dose-reduced group. 24 We were, however, limited by the retrospective nature of the study and it was not possible to test this hypothesis. Since most dose reductions occurred during induction and the first maintenance cycle, it is also possible that vincristine plays a major role in initial tumor control.…”
Section: Discussionmentioning
confidence: 99%